Implementation Of Dark And Raining Environmental Conditions To Investigate Lane Support System Performance For Passenger Cars In Southeast Asia: Case Study For Malaysian Domestic Road - Mansor, Muhd Ridzuan; Omar, Ghazali; Tamaldin, Noreffendy; Abdul Hamid, Nurfaizey; Md. Saad, Adzni; Arshad, M. A.; Akop, Mohd Zaid; Salim, Mohd Azli; Masripan, Nor Azmmi; Majid, M. H.A.; Maamor, M. A. H. M.; Herawan, S. G.; et al. (Praise Worthy Prize, 2021)
This paper presents a study on the implementation of dark and raining environment test conditions to investigate Lane Support System (LSS) performance for passenger cars in Southeast Asia. The case study has been performed for Malaysian domestic roads. LSS systems involved have been the Lane Departure Warning (LDW) and Lane Keep Assist (LKA). The literature review conducted has revealed that there is not yet a similar study performed for vehicle LSS system. The motivation of this study has been to identify the effect of both environmental conditions on the vehicle LSS performance. This pioneering work is also aimed to help in establishing a new LSS test protocol that could reflect better the driving situations in Southeast Asia countries. The experimental works have been carried out at state road in Melaka, Malaysia. LSS on-road test parameters have been adopted from LSS test protocols from the European New Car Assessment Programme (Euro NCAP) and the Japan National Agency for Automotive Safety and Victim’s Aid (NASVA). A new test procedure to carry out the study has been also developed in this study in order to complement the referred test protocols, including customized rain-making testing equipment to simulate the raining environment conditions. Results from the study have showed that both LDW and LKA systems performance could successfully be evaluated when subjected to dark and raining environment conditions using the new test procedure. Furthermore, the new test procedure developed in this study is also highly applicable for implementation in future LSS on-road tests involving any type of road category (both domestic and highway) with minimal setting up process